2021
DOI: 10.3390/vaccines9111286
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Receive the Booster COVID-19 Vaccine Dose in Poland

Abstract: COVID-19 vaccinations are essential to mitigate the pandemic and prevent severe SARS-CoV-2 infections. However, the serum antibody levels in vaccinated individuals gradually decrease over time, while SARS-CoV-2 is undergoing an evolution toward more transmissible variants, such as B.1.617.2, ultimately increasing the risk of breakthrough infections and further virus spread. This cross-sectional online study of adult Poles (n = 2427) was conducted in September 2021 (before a general recommendation to administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
210
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(271 citation statements)
references
References 58 publications
32
210
5
2
Order By: Relevance
“…This study revealed that a high proportion (71.3%) of the Czech HCW favour the COVID-19 vaccine BD, while 12.2% are still hesitant and 16.6% are against the currently available BD. These results are consistent with what had been recently reported by Rzymski et al 2021, who found that 71% of the Polish adult population declared their willingness to receive a COVID-19 vaccine BD, while the rest were not in favour of BDs [23]. In Japan, Sugawara et al 2021 revealed that 89.1% of Japanese medical students were willing to receive the hypothetical BDs of COVID-19 vaccines [85].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This study revealed that a high proportion (71.3%) of the Czech HCW favour the COVID-19 vaccine BD, while 12.2% are still hesitant and 16.6% are against the currently available BD. These results are consistent with what had been recently reported by Rzymski et al 2021, who found that 71% of the Polish adult population declared their willingness to receive a COVID-19 vaccine BD, while the rest were not in favour of BDs [23]. In Japan, Sugawara et al 2021 revealed that 89.1% of Japanese medical students were willing to receive the hypothetical BDs of COVID-19 vaccines [85].…”
Section: Discussionsupporting
confidence: 86%
“…Vaccine hesitancy (VH) is defined by the World Health Organization (WHO) Strategic Advisory Group of Experts on Immunization (SAGE) as "delay in acceptance or refusal of vaccination despite the availability of vaccination services" [22]. COVID-19 vaccine BD hesitancy (VBH) can be predicted in populations with suboptimal vaccine uptake, such as in Poland, where only 51% of the population received a first dose until the middle of September 2021, despite the extensive scientific communication efforts and the worsening epidemic situation in the country in 2021 [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A notable finding was that the hesitancy towards the booster dose was low among the responders since 24.7% of the sample were classified as hesitant with a total VHS score ≥25. Other surveys have found varying proportions of participants willing to receive the booster dose with values of 55.3% among HCWs in Saudi Arabia [13], 61.8% in adult Americans [14], 71% among adults in Poland [10], 71.3% among HCWs in Czechia [15], 83.6% a hypothetical yearly booster vaccine among healthcare workers in the United States [12], 84.5% among medical students in Japan [11], and 91.1% in the general population in China [16]. In the present study interviewees highlighted that the most common reasons in vaccine-related decision-making were because they would protect themselves and their relatives.…”
Section: Discussionmentioning
confidence: 99%
“…Hesitancy and willingness in relation to the COVID-19 vaccination have been investigated in different groups worldwide with a number of individuals who would either be unwilling to receive it or refuse it altogether despite the severity of the disease [8,9]. However, little is known yet about the intention to receive the booster dose [10][11][12][13][14][15][16]. In this current scenario, this is a challenging issue.…”
Section: Introductionmentioning
confidence: 99%